Sitting duck or scaredy-cat?: effects of shot execution strategy on anxiety and police officer's shooting performance under high threat - Nieuwenhuys, Arne (Legal and criminological psychology, 2017)
Purpose. Law enforcement may require police officers to inhibit intuitive responses to high threat and thereby affect their emotional reaction and operational effectiveness. Upon this premise, the current study reports two experiments which compare the impact of two relevant shot execution strategies on police officers’ shooting performance under high threat, including (1) fire at an armed assailant and then step away from the assailant's line of fire (‘fire-step’) or (2) step away from the assailant's line of fire and then fire (‘step-fire’). Method. In Experiment 1, 15 experienced police officers performed both shot execution strategies against a stationary assailant who occasionally shot back with coloured soap cartridges (high threat), while we measured their state anxiety, movement times and shot accuracy. In Experiment 2, the same 15 officers remained stationary and fired at the assailant who now performed both shot execution strategies in random order, thereby providing an indication of the risk (i.e., chance to get hit) associated with performing either strategy. Results. Experiment 1 showed that officers preferred using the step-fire strategy and that using this strategy resulted in lower levels of anxiety, increased time for aiming and more accurate shooting than the fire-step strategy. Experiment 2, however, indicated that the step-fire strategy also increases one's chance of getting hit. Conclusions. Findings suggest that inhibition of preferred responses under high threat (as in the fire-step strategy) may increase state anxiety and negatively affect shooting performance in police officers. Future work is needed to reveal underlying mechanisms and explore implications for practice.